ANALISIS PENERAPAN GOOD MANUFACTURING PRACTICES (GMP): STUDI KASUS DI DUA INDUSTRI PEMBEKUAN IKAN DI DENPASAR BALI - Resti Nurmala Dewi; Ni Putu Ayu Dyah Muncani; Ni Putu Dinda Krisna Putri (Jurnal Perikanan Unram, 2024)
One of the quality control systems that is crucial to establish for fisheries products is good manufacturing practices (GMP). Nonetheless, a number of fisheries processing sectors, including the seafood freezing sector, continue to have multiple GMP deviations. Therefore, the purpose of this study is to examine how GMP is being applied to two fish freezing companies that process sea bass (Lates calcarifer) and tuna (Thunnus albacares) in Denpasar, Bali. Using the gap analysis approach based on Minister of Industry Regulation Number 75 of 2010 concerning GMP, this research was conducted for three months (January – March 2022). The methods used for gathering data were focus groups discussion (FGD), observations, and interviews with managers, supervisors, and quality control (QC). From the research results, it was found that the implementation of GMP in the two fish freezing industries had met the criteria based on applicable regulations with a conformity percentage of 97.70% (tuna) and 98.39% (sea bass). As for the 18 GMP aspects, there are several deviations that occur in tuna freezing factories (6 aspects) and sea bass (4 aspects). Thus, improvements need to be made to aspects of buildings, sanitation facilities, process supervision, laboratories, employees as well as maintenance and sanitation based on the technical and managerial recommendations provided.